Haptic size perception is influenced by body and object orientation - M. McManus; L. R. Harris; K. Fiehler (Scientific Reports)
Abstract Changes in body orientation from standing have been shown to impact our perception of visual size. This has been attributed to the vestibular system’s involvement in constructing a representation of the space around our body. In the current study we investigated how body posture influences haptic size perception. Blindfolded participants were tasked with estimating the felt length of a rod and then adjusting it back to its previously felt size (after it had been set to a random length). Participants could feel and adjust the rod in the same posture, standing or supine, or after a change in posture. If the body orientation relative to gravity impacts size perception, we might expect changes in haptic size perception following body tilt. In support of this hypothesis, after changing between standing and supine postures there was a change in the rod’s haptically perceived length but only when the orientation of the rod itself also changed with respect to gravity but not when its orientation was constant. This suggests that body posture influences not only visual but also haptic size perception, potentially due to the vestibular system contributing to the encoding of space with respect to gravity.